EMPLOYEE REWARDS POLICY AND ITS INFLUENCE ON ORGANISATIONAL PERFORMANCE - Dr. Cross Ogohi Daniel (International Journal of Research Science and Management, 2019)
Reward Policy is very important for the performance of the employees. Therefore they are very important for the organization too. The purpose of this research is to measure the Effects of Employee Rewards Policy on Organisation Performance. A questionnaire was designed to collect the data on the factors related to reward policy like salary, promotion, Indirect Compensation and employee performance. The data was collected from different hospitality firms in Abuja namely hotel rosebud, sun heaven, summit villas. The data collected were analyzed in SPSS 25.00 Version. Different analytical and descriptive techniques were used to analyze the data.It is founded from different results that reward policy has positive impact on employee performance. It is proved from correlation analysis that all the independent variables have weak or moderate positive relationship to each other. Regression analysis shows that all the independent variables have insignificant and positive impact on employee performance. Descriptive analysis also reveals that all the independent variables have positive impact on employee performance. The major limitation of this research is that this study only covers the hospitality sector. Another limitation is that it excludes many variables of reward due to shortage of time. Funds were also another limitation. Apart from these limitations this research may provide insights to the managers to enhance the employee performance of their subordinates.